Conservação pelo uso e domesticação da feijoa na serra gaúcha – RS - Donazzolo, Joel (2012)
Farmers have tamed, handled and preserved the biodiversity elements for millennia in a co-evolution process. However, the intense environmental transformation has also caused intense genetic erosion and the associated traditional knowledge. It is in this content that this research is inserted into, and aimed to advance in the understanding of feijoa’s (Acca sellowiana (Berg) Burret) domestication process and also to promote its conservation through its use. Methodologically this study was based on participatory research and ethnobotany methods and was divided into three ways, interconnected and interdependent among themselves, with the purpose of concealing quantitative and qualitative approaches: (i) access and systematization of the local knowledge related to the use, management and conservation of feijoa and mapping elite plants on properties of family farmers, as well as residents in urban gardens in the Serra Gaúcha; (ii) genetic and phenotypic characterization of selected and managed plants by farmers, plants from urban gardens and those of spontaneous occurrence considered as natural populations, and (iii) establishment of a participatory plant breeding program aiming at the promotion of its use. The accessed traditional knowledge about use, management and conservation, is consistent and well distributed among the informants. To the farmers from Serra Gaúcha 10 distinct types of usage and 11 of management were identified. The main uses are related to food, medicine and commercialization. It was found three categories of farmers accordingly to their intensity of usage: growers, managers and maintainers, on which the Respondent Diversity Value (VDI) ranging between 0.41; 0.49; and 0.26, respectively (the last one differ significantly from the others). For the growers their VDI was also significantly different among the categories VDI=0.52). The farmers that were assisted by the Ecological Center (CE) showed a higher VDI (0.40) related to the use of feijoa than those not assisted. For those respondents from the urban gardens nine different types of use were identified and six different types of manage were related to it. A wide genetic and phenotypic diversity was found, especially in the selected and/or managed plants, what means that they are resources of extreme importance for on farm conservation and breeding programs. In general, the urban garden plants and those selected by the local farmers showed higher weight representing the main selection criterion. The weight of thousand seeds (PMS) ranged from 2.6788g to 6.0687g, being different from those found on the literature to this species. The genetic variation of feijoa is up to 90% in the samples here studied; all the samples showed a significant fixation index, except by the natural population. The magnitude and representativeness of the diversity found in the urban gardens in the town of Vacaria - RS reveals the need for these sites to be inserted in this specie conservation strategies, corresponding to a new conservation category called here “Urban Gardens”. The feijoa´s conservation in the studied region is reached through its systemic use. Participatory research directed to small households (as the Participatory Plant Breeding Program) seen to be effective to promote the specie’s use and conservation, because it was possible to define selections criterions, to evaluate the plant populations; to select and to multiply the promissory plants; to do the breeding and planning the assessment of the offspring. This study evidences revealed that A. sellowiana populations have being managed, cultivated, and in any level also selected and propagated in an anthropogenic landscape through at least hundred years. Thus, populations of the feijoa are under the domestication process in its own center of origin and diversity and can be considered as semi domesticated. However, the semi domesticated populations still have shown phenotypic variation that does not differentiated them from the wild populations. In fact, the feijoa is a species that have being accompanying the human beings, what means that if ceases the landscape management process feijoa will lose space for other species.